Review of microRNA detection workflows from liquid biopsy for disease diagnostics - Dulguunnaran Naranbat; Emilia Herdes; Nikos Tapinos; Anubhav Tripathi (Expert Reviews in Molecular Medicine)
MicroRNAs have emerged as effective biomarkers in disease diagnostics, particularly cancer, due to their role as regulatory sequences. More recently, microRNAs have been detected in liquid biopsies, which hold immense potential for early disease diagnostics. This review comprehensively analyses distinct liquid biopsy microRNA detection methods validated with clinical samples. Each step in the microRNA detection workflow, including sample collection, RNA isolation, processing, and detection of target microRNAs, has been thoroughly assessed. The review discusses the advantages and limitations of established and novel techniques in microRNA detection workflows, discussing their diagnostic capabilities and potential for future implementation at scale.